Effects of enriched environment on micturition activity in freely moving C57BL/6J mice. Issue 3 (1st March 2021) - Soeda, Fumio; Toda, Akihisa; Masuzaki, Kazuya; Miki, Risa; Koga, Takayuki; Fujii, Yukiko; Takahama, Kazuo
Abstract: Objectives: An enriched environment (EE) has been known to promote structural changes in the brain and enhance learning and emotional performance. However, little is known about the effect of an EE on brain stem functions, such as the micturition function. In this study, we examined whether an EE affects micturition activity in mice. Methods: Male C57BL/6J mice were used. We assessed the micturition activity of freely moving mice using a novel system developed in‐house. Results: During the dark period, but not light, the EE significantly increased voiding frequency, total voided volume, mean voided volume, voiding duration, mean flow rate, and maximum flow rate compared with the control environment. This EE effect on micturition function was associated with habituation to novel environments in the open‐field test, but not with amelioration of motor coordination in the rotarod test. Interestingly, even after the mice were withdrawn from the EE, the improvements in micturition function persisted, while other behavioral changes were abolished. The relative value of voiding frequency and total voided volume during the light period, expressed as a percentage of 24 hours, increased with age when mice were reared in a standard environment. However, this age‐related change was not observed in mice reared in an EE. Conclusions: These results suggest that an EE may promote micturition activity during the active phase of C57BL/6J mice, and its effects persist even after withdrawal from the EE. Furthermore, an EE may mitigate dysfunctions in micturition activity, such as polyuria, during the resting phase in aged mice.